Glocalization vs. Grobalization: a Key Challenge for Contemporary Sociology - Drakulovska Chukaleska, Marija; Dragovikj, Anica (My University, 2017)
In this paper, we analyze the explicative power and the practical relevance of two theoretical perspectives which are of utmost importance for more adequate understanding of our situation and our predicament in the modern world. Тhe first one is the theory of glocalization which refers to the ”mix of global and local” (Robertson, 2001, 1992; Roudometof, 2016; Ritzer, 2007, 2010). According to Robertson (1995, p. 28), the concept of glocalization in business life originated from micro-marketing, more precisely from the advertisement of goods and services in various local environments and markets. It is a known strategy of the capitalistic system in which there is an increased adjustment of global markets to local markets and cultures or “global localization” in the opinion of Robertson (Robertson, 1992, p. 173). Ronald Robertson (2001, pp. 465-466), referring to the relation between the global and the local, points out the mixture of the global and the local in various geographical areas, from which the process of glocalization comes out. The second one is the theory of grobalization which refers to the imperialistic ambitions of nations, corporations, organizations, and the like, while their desire indeed need to impose themselves on various geographic areas (Ritzer, 2007, p. 15). The term implies that these entities seek to have their power, influence, and in many cases profits grow (hence the term grobalization). The term was created as a counterpart to glocalization, or “the interpenetration of the global and the local, resulting in unique outcomes in different geographic areas” (Ritzer, 2007, p. 13).
Keywords: globalization, glocalization, grobalization, global-local, global society